PATIENT SAFETY CULTURE IN DIALYSIS SERVICES DURING THE COVID-19 PANDEMIC: NURSING PERSPECTIVE - Hoffmann, Marília Alves; Menezes, Aline Carrilho; Azevedo, Cissa; Amaral, Fabrícia Moreira Amorim; Rodrigues, Tatiana Aparecida; Ribeiro, Helen Cristiny Teodoro Couto; Mata, Luciana Regina Ferreira da (Cogitare Enfermagem, 2023)
Objective: to evaluate the patient safety culture from the perspective of nursing staff in dialysis services in the context of the COVID-19 pandemic. Method: cross-sectional study with 56 nursing professionals from three dialysis services in Minas Gerais - Brazil, between March and June 2021. The Hospital Survey on Patient Safety Culture instrument was used. The data were analyzed by descriptive and inferential statistics; chi-square test; and Generalizable Estimating Equations (p≤0.05). Results: Patient safety was rated as good or excellent by 69.6% of participants. The dimension "Expectations and actions of the service management that favor safety" was considered a strength (85.42%). "Non-punitive response to errors" (23.99%) and "Staff sizing" (45.83%) were considered weak. There was a higher percentage of positive responses in public and philanthropic services (p<0.001). Conclusion: few dimensions indicated strengths, and the type of management influenced the percentage of positive responses.